LIFE STORY OF PATIENT WITH SUPERVISION’S FIGHTING AGAINST COVID-19 IN SURAKARTA INDONESIA - Demartoto, Argyo; Sunesti, Yuyun; Haryono, Bagus; Mundayat, Aris Arif (Jurnal Analisa Sosiologi, 2020)
Life story of Covid-19 survivors aims to educate the people through patients’ testimony about experience with Covid-19 infection symptoms and the treatment they got in Surakarta Indonesia. The qualitative research with this biographic approach was conducted based on life story of Patients with Supervision (Pasien Dalam Pengawasan / PDP) using purposive sampling technique, so that the informants selected were PDP recovered from Covid-19, PDP’s family, friend, neighbor, Surakarta people, Pulmonologist and nurse in Dr. Moewardi Hospital of Surakarta, Chief Executive of Covid-19 Management Acceleration Task force of Surakarta, and Chairperson of Surakarta Health Office. The author collected primary and secondary data using online observation, in-depth interview and documentation. To validate data, method and data source triangulations were used. Data obtained was analyzed using an interactive model of analysis using Bandura’s Social Learning theory. Considering the patients’ experience, it can be seen that they are healed from Covid-19, because they were disciplined and complied with the procedure of treatment for Covid-19 patients. It can inspire and encourage other patients to keep fighting for their recover; to keep thinking positively, and to be sure that they will be healed, to follow the health protocol for coping with Covid-19, and to improve spirituality by getting closer to God.Keywords: life story, Patient with Supervision, Covid-19 AbstrakKisah hidup pasien yang sembuh dari Covid-19 bertujuan mengedukasi masyarakat melalui testimoni pengalaman pasien selama mengalami gejala serangan Covid-19 hingga selama perawatan di Surakarta Indonesia. Penelitian kualitatif dengan pendekatan biografi ini diambil dari kisah hidup Pasien Dalam Pengawasan (PDP) menggunakan teknik purposive sampling, sehingga informan yang dipilih adalah PDP yang sudah sembuh dari Covid-19, keluarga PDP, teman, tetangga, masyarakat Surakarta, Dokter Spesialis Paru dan perawat di RSUD Dr. Moewardi Surakarta, Ketua Pelaksana Gugus Tugas Percepatan Penanganan Covid-19 Kota Surakarta dan Kepala Dinas Kesehatan Kota Surakarta. Peneliti mengumpulkan data primer dan sekunder dengan observasi, wawancara mendalam dan dokumentasi melalui daring. Untuk menguji validitas data digunakan triangulasi metode dan sumber data. Data yang diperoleh dianalisis dengan menggunakan Model Analisis Interaktif dan teori Mekanisme Survival dari Scott. Pengalaman pasien yang berhasil sembuh dari Covid-19, karena selama menjalani perawatan pasien Covid-19 disiplin dan patuh. Hal ini dapat menjadi inspirasi dan dorongan bagi pasien lain untuk terus berjuang agar sembuh; selalu berpikir positif dan yakin untuk sembuh; mengikuti protokol kesehatan penanganan Covid-19; serta meningkatkan spriritualitas dengan lebih mendekatkan diri kepada Tuhan.Kata kunci: Kisah Hidup, Pasien Positif, Covid-19